2014
DOI: 10.1111/imm.12305
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin prevents lipopolysaccharide‐induced acute lung injury and inflammation in mice via peroxisome proliferator‐activated receptor gamma‐mediated attenuation of the nuclear factor‐kappaB pathway

Abstract: SummaryAcute lung injury (ALI) from a variety of clinical disorders, characterized by diffuse inflammation, is a cause of acute respiratory failure that develops in patients of all ages. Previous studies reported that wogonin, a flavonoid-like chemical compound which was found in Scutellaria baicalensis, has anti-inflammatory effects in several inflammation models, but not in ALI. Here, the in vivo protective effect of wogonin in the amelioration of lipopolysaccharide (LPS) -induced lung injury and inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 67 publications
4
47
0
Order By: Relevance
“…The leakage of protein rich plasma into alveolar space due to the upregulation of pulmonary barrier permeability results in lung edema. In this study, we found that lung edema was induced by LPS and this result was similar to previous study (Yao et al, ). At the same time, Yao et al has also demonstrated that the increased protein concentration in BALF after intravascular administration of LPS for 24 h is inhibited by wogonin at 30 mg/kg.…”
Section: Discussionsupporting
confidence: 92%
“…The leakage of protein rich plasma into alveolar space due to the upregulation of pulmonary barrier permeability results in lung edema. In this study, we found that lung edema was induced by LPS and this result was similar to previous study (Yao et al, ). At the same time, Yao et al has also demonstrated that the increased protein concentration in BALF after intravascular administration of LPS for 24 h is inhibited by wogonin at 30 mg/kg.…”
Section: Discussionsupporting
confidence: 92%
“…Comparable anti-inflammatory actions have been previously reported in several in vivo models of endotoxemia when using flavonoid-rich plant extracts, as well as for isolated flavonoids or their metabolites [25], [26], [27], [28], [29]. Regarding the actions of ( − )-epicatechin, we have previously reported that in fructose-fed and in high fat-fed rats inflammatory markers were mostly normalized by the presence of (−)-epicatechin in the diet [30], [31].…”
Section: Discussionmentioning
confidence: 61%
“…The pieces of colonic tissue were used for ex vivo analysis. The histological analysis was performed as previously described [48]. …”
Section: Methodsmentioning
confidence: 99%